6-4=2
5-X=?
5-2=3
X=3
That is the answer, sorry if i didn't explain it well<span />
5(x + 1)....distribute the 5 thru the parenthesis...that means multiply the 5 by everything in the parenthesis.
5(x + 1) = 5 * x + 5 * 1 = 5x + 5
Answer:
<h3>a. </h3>
Step-by-step explanation:
this my answer is perfect yap
Answer:
0.8 kilowatt/hour
Step-by-step explanation:
divide 4/5, gives you .
Graph the line y=5x. Then graph the line y=x. Then look at them and describe in what ways they are the same or different.